Broke - Heller, Mandasue (London Hodder & Stoughton, 2013)
Amy's marriage to Mark isn't the best--he can't resist the girls, he can't hold down a job. But she doesn't want to know just how bad things are until his gambling habit brings the debt collector to her door. He makes it brutally clear how she can pay off Mark's debts--and Amy's troubles are only beginning. Someone else wants Mark for herself, and she is ready to steal Amy's man, her self-respect and even her children. As the stakes rise, Amy will either lose everything, or she'll have to learn how to be as hard and ruthless as her enemies
Keywords: Married women -- Prostitution -- Drug addiction